Mitochondrial Cardiomyopathy Caused by Elevated Reactive Oxygen Species and Impaired Cardiomyocyte Proliferation. Issue 1 (5th January 2018) - Zhang, Donghui; Li, Yifei; Heims-Waldron, Danielle; Bezzerides, Vassilios; Guatimosim, Silvia; Guo, Yuxuan; Gu, Fei; Zhou, Pingzhu; Lin, Zhiqiang; Ma, Qing; Liu, Jianming; Wang, Da-Zhi; et al.
Abstract : Rationale: : Although mitochondrial diseases often cause abnormal myocardial development, the mechanisms by which mitochondria influence heart growth and function are poorly understood. Objective: : To investigate these disease mechanisms, we studied a genetic model of mitochondrial dysfunction caused by inactivation of Tfam (transcription factor A, mitochondrial), a nuclear-encoded gene that is essential for mitochondrial gene transcription and mitochondrial DNA replication. Methods and Results: : Tfam inactivation by Nkx2.5 Cre caused mitochondrial dysfunction and embryonic lethal myocardial hypoplasia. Tfam inactivation was accompanied by elevated production of reactive oxygen species (ROS) and reduced cardiomyocyte proliferation. Mosaic embryonic Tfam inactivation confirmed that the block to cardiomyocyte proliferation was cell autonomous. Transcriptional profiling by RNA-seq demonstrated the activation of the DNA damage pathway. Pharmacological inhibition of ROS or the DNA damage response pathway restored cardiomyocyte proliferation in cultured fetal cardiomyocytes. Neonatal Tfam inactivation by AAV9-cTnT-Cre caused progressive, lethal dilated cardiomyopathy. Remarkably, postnatal Tfam inactivation and disruption of mitochondrial function did not impair cardiomyocyte maturation. Rather, it elevated ROS production, activated the DNA damage response pathway, and decreased cardiomyocyte proliferation. We identified a transient window during the first postnatal week when inhibition of ROS or the DNA damage response pathway ameliorated the detrimental effect of Tfam inactivation. Conclusions: : Mitochondrial dysfunction caused by Tfam inactivation induced ROS production, activated the DNA damage response, and caused cardiomyocyte cell cycle arrest, ultimately resulting in lethal cardiomyopathy. Normal mitochondrial function was not required for cardiomyocyte maturation. Pharmacological inhibition of ROS or DNA damage response pathways is a potential strategy to prevent cardiac dysfunction caused by some forms of mitochondrial dysfunction. Abstract : Supplemental Digital Content is available in the text.